Hemodynamic parameters and neurogenic pulmonary edema following spinal cord injury: an experimental model Parâmetros hemodinâmicos e edema pulmonar neurogênico após traumatismo raquimedular: modelo experimental - Manoel Baldoino Leal Filho; Rosana C. Morandin; Amanda R. de Almeida; Elizabeth C. Cambiucci; Konradin Metze; Guilherme Borges; José Antonio Rocha Gontijo (Arquivos de Neuro-Psiquiatria)
Neurogenic pulmonary edema is a serious and always life-threatening complication following several lesions of the central nervous system. We report an experiment with 58 Wistar-Hanover adult male rats. Two groups were formed: control (n=4) and experimental (n=54). The experimental group sustained acute midthoracic spinal cord injury by Fogarty’s balloon-compression technique containing 20µL of saline for 5, 15, 30 or 60 seconds. The rats were anesthetized by intraperitoneal (i.p.) sodium pentobarbital (s.p.) 60 mg/Kg. The quantitative neurological outcome was presented at 4, 24 and 48 hours from compression to characterize the injury graduation in different groups. Poor outcome occurred with 60 seconds of compression. Six animals died suddenly with pulmonary edema. Using the procedure to investigate the pulmonary edema during 60 seconds of compression, followed by decompression and time-course of 60 seconds, 20 rats were randomly asigned to one of the following groups: control (1, n=4, anesthetized by i.p. s.p., 60 mg/Kg but without compression) and experimental (2, n=7, anesthetized by i.p. xylazine 10 mg/Kg and ketamine 75 mg/Kg) and (3, n=9, anesthetized by i.p. s.p., 60 mg/Kg). The pulmonary index (100 x wet lung weight / body weight) was 0.395 ± 0.018 in control group, rose to 0.499 ± 0.060 in group 2, and was 0.639 ± 0.14 in group 3. Histologic examination of the spinal cord showed parenchymal ruptures and acute hemorrhage. Comparison of the pulmonary index with morphometric evaluation of edema fluid-filled alveoli by light microscopy showed that relevant intra-alveolar edema occurred only for index values above 0.55. The results suggest that the pulmonary edema induced by spinal compression is of neurogenic nature and that the type of anesthesia used might be important for the genesis of lung edema. Edema pulmonar neurogênico é complicação séria e aumenta o risco de vida em pacientes com várias lesões do sistema nervoso central. Apresentamos uma experiência com 58 ratos Wistar machos e adultos. Foram formados dois grupos: controle (n=4) e experimental (n=54). O grupo experimental sofreu trauma raquimedular torácico médio com o cateter-balão de Fogarty contendo 20µL de salina por 5, 15, 30 ou 60 segundos de compressão. Os ratos foram anestesiados com pentobarbital sódico (p.s.), 60 mg/Kg intraperitoneal (i.p.). Foi investigada a relação entre a lesão medular e o tempo de compressão. A evolução neurológica foi quantificada e apresentada com 4, 24 e 48 horas da compressão para caracterizar a graduação da lesão nos diferentes grupos. A pior evolução ocorreu com 60 segundos de compressão. Seis animais morreram subitamente com edema pulmonar. Vinte ratos foram randomicamente distribuídos em um dos seguintes grupos: controle (1, n=4, anestesiados com p.s. i.p., 60 mg/Kg, mas sem compressão) e experimental (2, n=7, anestesiados com xilasina 10 mg/Kg e ketamina 75 mg/Kg) e (3, n=9, anestesiados com p.s. i.p., 60 mg/Kg). O índice pulmonar (100 x peso pulmonar / peso corporal) foi 0,395 ± 0,018 no grupo controle, 0,499 ± 0,060 no grupo 2, e 0,639 ± 0,14 no grupo 3. O exame histológico da medula espinhal mostrou rupturas no parênquima e hemorragia aguda. Comparando-se o índice pulmonar com o índice morfométrico através da microscopia óptica, evidenciou-se que ocorreu edema intra-alveolar relevante para índices acima de 0,55. A presente experiência sugere que o edema pulmonar induzido pela compressão medular é de natureza neurogênica e que o tipo de anestesia utilizada no experimento poderia ter participação na gênesis do edema pulmonar.